Out of bounds: factors affecting the perceived offensiveness of racial slurs. (November 2015) - O'Dea, Conor J.; Miller, Stuart S.; Andres, Emma B.; Ray, Madelyn H.; Till, Derrick F.; Saucier, Donald A.
Abstract: Racial slurs are terms used primarily to disparage individuals belonging to the targeted social group. In two studies, we manipulated racial slurs ("nigger", "nigga") used by White individuals toward Black individuals in different situations (between friends versus between strangers) to assess different levels of perceived offensiveness in White third party observers. Consistent with our hypotheses, in Study 1 we found that the use of racial slurs between friends was perceived to be less offensive than between strangers, and "nigga" was perceived to be less offensive than "nigger". In Study 2 we replicated these results, and extended them by finding that ratings of offensiveness, consistent with hypotheses, were correlated with individual differences relating to the justification and suppression of prejudice. Our findings suggest that observers' reactions to racial slurs depend on the context in which the slur is used and perceivers' beliefs about the social appropriateness of expressing prejudice. Highlights: We examined perceptions of and reactions to witnessing racial slurs. Perceived offensiveness of racial slurs varies depending on the slur used. Even extremely offensive slurs did not ceiling our measure of offensiveness. Reactions to racial slurs are related to beliefs about expressing prejudice. Racial slurs may function as both expressives and descriptives.